Clustered Carbon Monoxide Poisoning Cases: Accidental Poisoning In A Vehicle (Bangladesh Critical Care Journal, 2024)
Carbon monoxide (CO) is a product of combustion of organic matter in the presence of inadequate supply of oxygen. Common sources are burning fuel, engine exhaust, burning of animal dung, heater emissions and gas geyser. It is a toxic, clear, colorless and tasteless gas. The clinical presentation runs a spectrum, ranging from headache and dizziness to coma and death. Here we report three cases that presented to us in the month of November 2023 with history, sign & symptoms suggestive of CO poisoning.Bangladesh Crit Care J March 2024; 12 (1): 72-74